NEGOTIATING IDENTITY: THE AUTHOR’S USE OF CODE-SWITCHING IN THE NOVEL “THE SHELTER - Restuwati Azhar; Adi Sutrisno (University of Muhammadiyah Malang, 2023)
The existence of different languages in a multicultural society is one of the triggering factors for the occurrence of code-switching in both real life and literary works including novels. The objective of this study were to: 1) describe the forms and types of code-switching in Aydan Ahn’s novel “The Shelter”, and 2) describe the author’s intention to negotiate identity through code-switching. The research’s data consisted of a variety of utterances produced by characters that switch between Indonesian and Korean language. The analysis findings revealed that 23 occurrences of code-switching were found in conversations between characters in the novel. Twelve of them were inter-sentential switching, nine were of tag switching, and two were of intra-sentential switching. Speakers aim to accentuate the message the want to convey to their interlocutor, which is why code-switching occurs in the utterances produced by the characters. In addition, speakers also perform code-switching to complete the sentences or clauses they say. Meanwhile, from the writer's point of view, it can be concluded that the author tries to make the story written to be more alive. The code-switching was intended to negotiate the author’s identity through the expressions that expose the author’s cultural background knowledge.